2017
DOI: 10.1002/pits.22030
|View full text |Cite
|
Sign up to set email alerts
|

Academic growth expectations for students with emotional and behavior disorders

Abstract: Computer adaptive assessments were used to monitor the academic status and growth of students with emotional behavior disorders (EBD) in reading (N = 321) and math (N = 322) in a regional service center serving 56 school districts. A cohort sequential model was used to compare that performance to the status and growth of a national user base of more than 7,500,000 students without disabilities. Consistent with numerous previous findings, status or level of performance of students with EBD was consistently low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The research revealed that positive interactions is the means to successful planning and curriculum adaptations. Ysseldyke, et al (2017) conducted a study about the academic growth expectations for children with emotional and behaviour disorders. In this study computer adaptive assessments were used to monitor the academic status and growth of students with emotional and behaviour disorders (EBD) in reading (N = 321) and Mathematics (N = 322) in a regional service centre serving 56 school districts.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The research revealed that positive interactions is the means to successful planning and curriculum adaptations. Ysseldyke, et al (2017) conducted a study about the academic growth expectations for children with emotional and behaviour disorders. In this study computer adaptive assessments were used to monitor the academic status and growth of students with emotional and behaviour disorders (EBD) in reading (N = 321) and Mathematics (N = 322) in a regional service centre serving 56 school districts.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Executive Functioning, Self-Regulation, and Social Skills Social, emotional and behavioural competencies are crucial for success in the classroom (Andrews et al, 2001;Rosenberg, 2015) and are interrelated (Kilgus et al, 2017;Ysseldyke et al, 2017). Supports in these domains may be required for some students to make the age appropriate academic skill gains of which they are capable (Ysseldyke et al, 2017).…”
Section: Verbal Communication Visual Cognitive and Literacymentioning
confidence: 99%
“…Supports in these domains may be required for some students to make the age appropriate academic skill gains of which they are capable (Ysseldyke et al, 2017). There are many examples of literature and methods available to aid school personnel in supporting student executive functioning (Dawson and Guare, 2003), self-regulation (Shanker, 2012;Woodward et al, 2017), and social skills (Reid et al, 2007;Frankel and Whitham, 2011).…”
Section: Verbal Communication Visual Cognitive and Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, relative to their nonidentified peers, students identified as ED face increased probabilities for juvenile delinquency, incarcerations, and substance abuse (e.g., Barnett, 2012;Bradley, Doolittle, & Bartolotta, 2008). Academically, these students demonstrate limited growth in their achievement, often resulting in academic deficits across multiple areas that do not show improvement over time (e.g., Rice & Yen, 2010;Ysseldyke et al, 2017). Given their struggles to learn at a commensurate level with their peers, it is not surprising that students with ED are at significantly higher probability for school failure and school dropout (e.g., Bradley et al, 2008;Merrell & Walker, 2004;Sullivan & Sadeh, 2016) and subsequently exhibit more difficulties adjusting to life as adults than students in other disability categories (e.g., Bradley, Henderson, & Monfore, 2004;Carter & Wehby, 2003;Frank, Sitlington, & Carson, 1995).…”
Section: Implications Of the Current Ed Definition For Studentsmentioning
confidence: 99%